Vascular, Nerve, and Tendon Injuries of the Extremities in Disaster and Earthquake Treatment - Aydın, Servet Yekta; Demiröz, Anıl (Cerrahpaşa Medical Journal, 2023)
Extremities are prone to trauma because they are projections of the body. In closed injuries, there is usually no need for an immediate final surgery. The exception is the presence of a circulatory disorder that will cause the loss of a limb. If there is bleeding, the priority in treatment should be to stop it. Compression should be applied to stop bleeding, and the affected extremity should be elevated above the level of the heart. While copious irrigation, primary closure, and splint can be applied, if primary closure is not possible, it would be appropriate to apply a splint after sterile dressing with moist absorbent gauze. In case of amputations, it is appropriate to wrap the amputate in a gauze moistened with saline, which is important in the transfer of the amputate, and then put it in a waterproof bag and place it in another bag in ice water in the ice bag. Cite this article as: Aydın SY, Demiröz A. Vascular, nerve, and tendon injuries of the extremities in disaster and earthquake treatment. Cerrahpaşa Med J 2023;47(S1):62-63.